The Journals of Jeffery Amherst, 1757-1763, Volume 1 : The Daily and Personal Journals - Amherst, Jeffery Amherst, Baron, 1717-1797 (Book collections on Project MUSE., 2015)
General Jeffery Amherst served as commander in chief of the British army in North America during the Seven Years' War from 1758 until 1763. Under Amherst's leadership the British defeated French forces enabling the British Crown to claim Canada. Like many military officers, Amherst kept a journal of his daily activities, and the scope of this publication is from March 1757, while he was Commissary to the troops of Hesse-Kassel on British service in Germany, until his return to Great Britain in December 1763. The daily journal contains a record of and a commentary on events that Amherst witnes.